Management accounting practices: a bibliometric analysis / Salumah Nain, Nelson Lajuni and Rasid Mail - Nain, Salumah; Lajuni, Nelson; Mail, Rasid (Universiti Teknologi MARA, 2022)
The study of management accounting practices began 40 years ago, and regarded as an important issue in management accounting. Management accounting strategies have evolved to meet the need to adapt to changes in the industrial and macroeconomic climate. Theoretical and realistic aspects of management accounting approaches were built to meet the needs of timely and effective decision-making. In this study, journals publish management accounting research and most cited sources in these journals were explored by performing a bibliometric analysis on scientific literature published in the field of management accounting practices. The Scopus database was used to gather literature related on management accounting practices. Apart from employing SPSS and Microsoft Excel software, Publish or Perish software was also utilized to integrate the data and perform simple analysis before using the VOSviewer to perform data visualisation. Publication’s growth, the productivity of research and citation analysis were reported via standard bibliometric analysis. A total of 321 documents were retrieved based on the keyword search results. Most articles were written in English and published in journals and conferences articles. The bibliometric analysis presents the advancement of the scientific literature on management accounting practices and highlights the areas of interest where future researchers could explore.